Social exclusion evokes different psychophysiological responses in individuals high on the psychopathy facets fearless dominance and self-centered impulsivity - Seeger, Natalia A.; Brackmann, Nathalie; Lamm, Claus; Hennig-Fast, Kristina; Pfabigan, Daniela M. (Frontiers in Psychiatry, 2024)
Individuals with psychopathic personality traits are generally thought to have difficulties in processing and experiencing emotions. These difficulties could also translate to emotionally charged social situations such as social exclusion. Being socially excluded is often experienced as stressful and unpleasant, potentially even leading to selfish or aggressive behavior–both of which are linked to certain aspects of psychopathy. The current study investigated self-report and physiological responses to social exclusion in the cyberball paradigm in a carefully selected community sample of individuals either scoring high on primary (N = 24) or secondary psychopathy traits (N = 17). Across the sample, the cyberball paradigm decreased experiences of joy and approach motivation, increased subjective anger reports, and induced changes in heart rate. In contrast, individuals scoring high on secondary psychopathy traits (Self-Centered Impulsivity group) displayed stronger physiological reactivity during a habituation phase of prolonged social exclusion than individuals scoring high on primary psychopathy traits (Fearless Dominance group), indexed by changes in skin conductance level. Moreover, a potential mismatch between self-reported and physiological arousal seemed to be only observable in individuals with high secondary psychopathy traits. Overall, the current results suggest diverging patterns of emotional processing and regulation in a social exclusion situation when comparing well-functioning individuals with varying psychopathy traits. It seemed as if individuals high on primary psychopathy traits were insensitive to contextual social cues, while individuals high on secondary psychopathy traits were more affected by the potentially threatening social situation. Cautiously transferring the current findings to forensic samples, they support the idea of moving from a behavioral understanding of the psychopathy construct to a more clinical picture with distinct cognitive and emotional processing patterns in individuals high on either primary or secondary psychopathy traits.